2017
DOI: 10.4081/jphia.2017.557
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and cultural beliefs of mothers regarding the risk factors of infant hearing loss and awareness of audiology services

Abstract: The aim of the paper is to describe the knowledge of mothers in Durban, South Africa, regarding risk factors of hearing loss in infants and their awareness of audiology services, and to describe their cultural beliefs about the risk factors for hearing loss in infants. A descriptive survey design with quantitative methods of analysis were used. Conveniently sampled mothers (n=102) receiving postnatal care for their infants from eight provincial clinics within Durban consented to participate, yielding a respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
2
13
1
Order By: Relevance
“…14 Similarly, approximately 79% of respondents were aware that their child's ototoxic medicine and middle ear infections would lead to hearing loss. 16 Moreover, it can be noted that the hearing loss awareness of individuals older than 25 was significantly better than the younger age group of≤25 years) (p<0.001). We further observed that, married respondents were significantly more associated with having better awareness toward hearing loss (p<0.001).…”
Section: Discussionmentioning
confidence: 92%
“…14 Similarly, approximately 79% of respondents were aware that their child's ototoxic medicine and middle ear infections would lead to hearing loss. 16 Moreover, it can be noted that the hearing loss awareness of individuals older than 25 was significantly better than the younger age group of≤25 years) (p<0.001). We further observed that, married respondents were significantly more associated with having better awareness toward hearing loss (p<0.001).…”
Section: Discussionmentioning
confidence: 92%
“…An overwhelming majority of the study participants will take their child to the clinic, doctor or audiologist if they suspect a hearing loss. Govender and Khan ( 2017 ) also supported this, but stated that more than 70% of the participants did not know that audiologists are the ones responsible for hearing aid prescription and fitting, as well as aural rehabilitation services. Only 45% of participants were aware that an audiologist is responsible for screening, assessing, diagnosing and managing hearing loss in both children and adults.…”
Section: Discussionmentioning
confidence: 96%
“…A study by Govender and Khan (2017), performed in urban KwaZulu-Natal, Durban central region, yielded different results with regard to cultural beliefs. Angry ancestors were noted by 60.8% of the participants and curses by 55.9% as being causes of hearing loss in their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Africa showed that over half of mothers were unaware that maternal rubella can lead to hearing loss. In addition, (78.4%) of the participants were aware that ototoxic medication consumed by their child and middle ear infections can result in hearing loss 11 .…”
Section: Introductionmentioning
confidence: 99%